Recurrent maternal CMV infection associated with symptomatic congenital infection: results from a questionnaire study in Portugal - Paulo Paixão; Maria João Brito; Daniel Virella; Maria Teresa Neto (BMJ Publishing Group, 2019)
Objective Human cytomegalovirus (CMV) is the most widespread agent of congenital infection in humans and is still a challenging issue. Despite lower rates of vertical transmission being associated with recurrent infection when compared with primary infection, the first still represents the majority of congenital infections worldwide. Based on data from active reporting, we explored the influence of maternal primary/non-primary infection both on the presentation and outcome of congenital CMV infection in early childhood.Design Infants with positive viruria during the first 3 weeks of life were reported through the Portuguese Paediatric Surveillance Unit.Patients Infants born between 2006 and 2011 with confirmed congenital CMV infection.Methods Maternal infection was considered primary if CMV IgG seroconversion occurred during pregnancy or low avidity IgG was documented; it was considered non-primary if positive IgG was documented before pregnancy or high avidity CMV IgG was present early in pregnancy. Follow-up questionnaires were sent up to 6 years of age.Results Forty confirmed cases of congenital CMV infection were reported (6.6:105 live births, 95% CI 4.81 to 8.92); 22 out of 40 were asymptomatic. The odds for non-primary maternal infection if the offspring was symptomatic at birth were 6.2 (95% CI 1.2 to 32.27).Conclusion The reported number of confirmed cases of congenital CMV infection was much lower than expected. Under-reporting and missed diagnosis were considered possible reasons. Non-primary maternal infections were associated with symptomatic congenital CMV infection in the offspring. Maternal recurrent infections can have a significant impact on the total number of symptomatic infections in Portugal.